Interpersonal stress, not depression or hopelessness, predicts suicidality in university students in Macao. (April 2014) - Zaroff, Charles Mark; Wong, Hon Lam; Ku, Lisbeth; Van Schalkwyk, Gertina
Objectives: Joiner's Interpersonal Theory of Suicide, which states that an individual will desire death when they perceive themselves to be a burden to others, and experience social isolation, has received much support, but has not been directly assessed in non-Eurocentric individuals. Methods: Joiner's Interpersonal Needs Questionnaire (measuring both perceived burdensomeness and thwarted belongingness) and measures of depression, hopelessness, gender, relationship status and region of residence were evaluated as risk factors for suicidality after controlling for response biases. Participants were 273 undergraduate university students of Chinese ethnicity between the ages of 17 and 23 years in Macao. Results: The predictors in sum distinguished between the presence and absence of suicidality (χ 2 = 62.759, p < .01). Perceived burdensomeness ( p < .01) and relationship status ( p < .01) made significant contributions to the presence of suicidality. Low internal consistency prevented thwarted belongingness from being assessed as a risk factor. Conclusions: Interpersonal variables may account for the seemingly disparate risk factors for suicide.